2014
DOI: 10.1002/bab.1231
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and evaluation of the effect of Fe3O4@piroctone olamine magnetic nanoparticles on matrix metalloproteinase‐2: A preliminary in vitro study

Abstract: In the present study, Fe3 O4 magnetic nanoparticles were synthesized by the coprecipitation of Fe(2+) and Fe(3+) ions and used as a nanocarrier for the production of piroctone-olamine-loaded Fe3 O4 nanoparticles (Fe3 O4 @PO NPs). The nanocrystalline structure of the prepared iron oxide species was confirmed by the X-ray diffraction spectroscopy method. Particle size distribution analysis showed that the size of Fe3 O4 @PO NPs was in the range of 5-55 nm. The magnetization curve of Fe3 O4 @PO NPs (with saturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…The results exhibited that the addition of gentamicin on the surface of the MNPs using SA significantly increased the size of the G@SA-MNPs compared with MNPs ( p < 0.05). Such effects have been previously reported for MNPs coated with other compounds, such as piroctone olamine and umbelliprenin (23, 24). Furthermore, the surfaces of the MNPs were saturated with the adsorbed linear SA, and this induced both hydration forces and electrosteric stabilization due to the hydrophilic character of linear SA and the presence of charged polyelectrolyte loops, respectively.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results exhibited that the addition of gentamicin on the surface of the MNPs using SA significantly increased the size of the G@SA-MNPs compared with MNPs ( p < 0.05). Such effects have been previously reported for MNPs coated with other compounds, such as piroctone olamine and umbelliprenin (23, 24). Furthermore, the surfaces of the MNPs were saturated with the adsorbed linear SA, and this induced both hydration forces and electrosteric stabilization due to the hydrophilic character of linear SA and the presence of charged polyelectrolyte loops, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Previously, Khorramizadeh et al (24) reported that each milligram of prepared umbelliprenin-coated MNPs contained almost 250 μg of umbelliprenin. Shakibaie et al reported the preparation of Fe 3 O 4 @piroctone olamine MNPs (without using polymers), which each 1 mg of the coated NPs contained 50 ± 1.3 μg of piroctone olamine (23). However, in the case of loading other antibiotics like amoxicillin on magnetic nanoparticles with Poly (lactide-co-glycolide) copolymer (PLGA) and Poly (lactide-co-glycolide)-polyethylene glycol copolymer (PLGA-PEG), the measured efficient entrapment was 90% and 48–52%, respectively (26).…”
Section: Discussionmentioning
confidence: 99%
“…These results show that Fe 3 O 4 @Chitosan-AgNPs can be developed as nanomaterials that are antibacterial. Previous studies have reported that Fe 3 O 4 NPs at a concentration of 120 µg/mL had no cytotoxicity effect on normal line Hs68 cells with 89% viability [ 18 ]. Zhang et al have also reported that although magnetic Fe 3 O 4 nanoparticles at sizes 120 and 250 nm at various concentrations do not have significant toxicity in chicken macrophage cells (HD11).…”
Section: Discussionmentioning
confidence: 99%
“…However, little evidence exists that nanomaterials themselves might possess intrinsic anticancer properties, and only a few nanoparticles’ intimate interactions with the tumour microenvironment were reported 13 14 15 16 17 . For example, Fe 3 O 4 nanoparticles coated with piroctone olamine 18 , fullerene-based nanomaterial Gd@C 82 (OH) 22 19 20 21 22 , hollow mesoporous carbon nanocapsules (HMCNs) 23 and polysaccharide-based hydrogels 24 have been found to exhibit inhibition of MMP activity. However, none have translated to clinical application due to the dose-limiting side effects following systemic administration of these pharmacological MMP inhibitors 24 .…”
mentioning
confidence: 99%